Melalui Pendidikan Agama Hindu Meningkatkan Sradha Mahasiswa di Kampus IHDN Denpasar - Si Luh Nyoman Seriadi (UHN IGB Sugriwa Denpasar, 2015)
Education is one of the fundamentals for the Hindus in this modern globalisation. As the increasing negative influence due to lacking of good religious values. This study discusses problems, such as (1) what is Faculty of Dharma Acarya (FDA)?; (2) what should be done to improve the facultyâ€; (3) what benefits would be there if the quality of the faculty increases? This study concluded that Hindu education should be aimed at improving the Sradha and Bhakti of the IHDN Denpasar students, the religious skills, and the intellectualities, building the characters, strengthening the personalities, and the loyalty to the country as well as to the Balinese own culture.